2009
DOI: 10.1142/s0218625x09013256
|View full text |Cite
|
Sign up to set email alerts
|

X-RAY INVESTIGATION OF Ti-DOPED HYDROXYAPATITE COATING BY MECHANICAL ALLOYING

Abstract: Ti -addition to hydroxyapatites [Ca10(PO4)6(OH)2–HA] with 5.0 wt.% Ti content, was successfully deposited on titanium substrate by mechanical alloying (MA) method. The X-ray Diffraction (XRD) data indicated that some changes take place in the HA lattice as well as in the Ti substrate. The coating thickness of the as-synthesized sample was about 91.1 μm. Ti incorporation into the apatite structure caused lattice shrinkage. The heat treated sample shows that dominant phase was HA up to 600°C. The Ti -doped HA st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…It was shown that significant decrease of the HA particle and crystalline size as a result of HEBM, leads to the formation of the nano-scale structure. The comparison of surface topography for composite substrates shows that one hour of HEBM with optimum ball to powder ratio equals to 40:1 leads to the reduction of surface particle size from 1.0 Pm to 80 nm [7,8]. Let us discuss these results in more details.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that significant decrease of the HA particle and crystalline size as a result of HEBM, leads to the formation of the nano-scale structure. The comparison of surface topography for composite substrates shows that one hour of HEBM with optimum ball to powder ratio equals to 40:1 leads to the reduction of surface particle size from 1.0 Pm to 80 nm [7,8]. Let us discuss these results in more details.…”
Section: Introductionmentioning
confidence: 99%
“…Coated SiHA on Ti substrate demonstrates the foundation of HA, as well as Si peaks. Comparison of these patterns with those obtained in [ 7 , 8 ] shows the influence of high-energy ball milling process on the structure stability of the formed phases.…”
Section: Resultsmentioning
confidence: 59%
“…Since kinetic solubility is dependent on particle size, there has been great interest in nanosized HA-based cement as bone substitute materials [ 5 , 6 ]. Our group also has recently described the effect of high energy ball milling treatment on HA and Ti substrate [ 7 , 8 ]. It was shown that, during this type of mechanical treatment, a significant decrease of the HAs' particle and crystalline size takes place which leads to formation of nanoscaled coating on the Ti substrate.…”
Section: Introductionmentioning
confidence: 99%
“…These include Ti/HA systems [11], HA/β-TCP [12], and HA/TiO 2 [13]. It is important to emphasise that in the widely used plasma spraying method for the application of coatings a continuous flame or plasma sputtering is used [14,15]. This can lead to undesirable overheating or melting of the particles and a significant substrate temperature increase, which is a major limitation of this method.…”
Section: Introductionmentioning
confidence: 99%